World Economy Autumn 2023: Global economy remains on track despite significant headwinds - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Nils Sonnenberg; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2023)
The global economy has expanded at a very moderate pace so far in 2023, but stayed clear of the recession predicted by many for the advanced economies as a result of the massive tightening of monetary policy. In the United States in particular, the economy is proving surprisingly robust. By contrast, economic momentum in China has recently fallen short of expectations and is likely to remain subdued amid structural problems. Overall, we expect global production - measured on a purchasing power parity basis - to increase by 3.0 percent this year, with growth next year likely to be somewhat lower at 2.8 percent. Compared with our June forecast, we have revised growth upward by 0.2 percentage points for 2023 and downward by 0.2 percentage points for 2024. For 2025, we expect the global economy to pick up to a growth rate of 3.2 percent. Unemployment in the advanced economies will increase slightly going forward, although it will remain low by historical standards. Inflation has recently fallen significantly, mainly as a result of lower commodity prices. While underlying inflation has remained high for the most part, we expect an easing of the situation to become increasingly apparent in the coming months. Nonetheless, inflation rates are not expected to fall sustainably to levels close to the targets before 2025.
Keywords: 330